Sistem Kendali Penerangan Gedung Berdasarkan Waktu dan Pengaturan Intensitas Cahaya Terintegrasi Internet Of Things - Rizky Adha; Angga Pradana; Muhammad Rizky Fajar; Wan Saddam Hasan; Roberto Kaban; Eriansyah Saputra Hasibuan; Tri Indah Prasasti (Prodi Teknik Informatika (S1) Institut Teknologi dan Bisnis Indonesia, 2023)
IoT (Internet of Things) is a concept that aims to expand the benefits of continuously connected internet connectivity. IoT (Internet of Things) can be used in buildings to control electronic equipment such as room lights that can be operated remotely via a computer network. The research was carried out by building a remote control device that utilizes TCP/IP to carry out control processes in the local network through a web server embedded in the remote control device. There are two control features, namely one lamp control that is used to turn on one lamp and the overall lamp control feature and turns on all the lights at once.